Diabetes, insulin resistance, and asthma: a review of potential links. Issue 1 (January 2021) - Wu, Tianshi David
Abstract : Purpose of review: Disorders of glucose metabolism, including insulin resistance, prediabetes, and diabetes, have been identified as risk factors for worsened asthma. This review summarizes emerging evidence for their role as modifiable risk factors in asthma, including the potential benefit of diabetes medications on asthma outcomes. Recent findings: Experimental studies show that hyperinsulinemia associated with insulin resistance is associated with airway smooth muscle proliferation and promotes contractility. Epidemiologic studies have identified a higher prevalence of glycemic dysfunction among those with severe and uncontrolled asthma, and longitudinal studies have associated prediabetes and diabetes with higher risk of asthma exacerbations. The potential benefits of thiazolidinediones (TZDs), glucagon-like peptide-1 agonists, and metformin being investigated in asthma, but thus far interventional studies of TZDs have reported null results. On the contrary, observational studies have inconsistently controlled for relevant confounders which leaves conclusions vulnerable to misattribution of relationships due to corelated metabolic disorders, including dyslipidemia. Summary: Developing evidence suggests that disorders of glucose metabolism may be associated with worsening asthma. However, these conditions arise within a network of obesity-related metabolic diseases that may themselves worsen asthma. Few interventional trials have not identified a benefit, but data have been limited. Additional research is needed to define the potential independent impact of disorders of glucose metabolism in asthma.